Atractylodin induces oxidative stress‐mediated apoptosis and autophagy in human breast cancer MCF‐7 cells through inhibition of the P13K/Akt/mTOR pathway. Issue 8 (28th April 2022) - Li, Zuowei; Song, YeLin; Hou, Wangjun; Qi, Yingzi; Lu, Xuxiang; Xue, Ye; Huang, Jie; Fang, Qiong
Abstract: This study aimed to determine the apoptosis and autophagy‐inducing mechanism of atractylodin in human breast cancer MCF‐7 cells. The molecular mechanism of anticancer activity of atractylodin was confirmed by assessing the levels of reactive oxygen species (ROS) level, lipid peroxidation (LPO), antioxidants activity, dual staining, and comet assay. Moreover, cleaved caspases 3, 8, and 9, and signaling proteins, such as p53, Bcl‐2, and Bax, phosphatidylinositol‐3‐kinase/protein kinase B/mammalian target of rapamycin(P13K/Akt/mTOR), LC3I and LC3II, and beclin‐1 were analyzed. In MCF‐7 cells treated with atractylodin, the concentration‐dependent toxicity, increased LPO, increased production of ROS, and decreased activity of superoxide dismutase, catalase, and glutathione peroxidasewere observed. In MCF‐7 cells, atractylodin administration decreased Bcl‐2 expression while activating the expression of p53, Bax, cleaved caspase‐3, caspase‐8, and caspase‐9 apoptotic members. Furthermore, atractylodin blocked the P13K/Akt/mTOR signaling pathway, increased the conversion of LC3I to its lipidated form of LC3II, and increased beclin‐1 expression, whereas downregulated the p62 expression in MCF‐7 cells. As a result, altering apoptotic and autophagy‐related biomarkers, atractylodin triggered apoptosis and autophagy in MCF‐7 cells. As a result, atractylodin could be utilized to treat human breast cancer after the proper clinical trial.